问题 解答题
7
8
-
15
32
÷
5
8
+
3
16
=______
4
3
-
1
5
×
1
4
)÷
4
15
=______
4
5
×
5
18
+
3
7
+
7
9
=______
7
8
÷〔(
7
8
-
3
4
)×
4
5
〕=______
6×(
2
15
+
1
12
)-
1
8
=______
2-
5
9
÷
2
3
-
1
6
=______
7
3
-(
3
5
÷
9
20
+
8
23
)=______
〔2-(
8
5
+
1
3
)〕÷
4
15
=______
1-(
5
8
÷
3
2
+
1
4
)=______
5
7
÷
8
9
+
7
8
÷
7
5
-
5
7
=______
(1-
1
3
÷
4
7
)×
3
10
=______
3
5
-
3
5
×
5
9
)÷
4
9
=______
5
6
-(
3
4
-
1
2
)〕÷
7
15
=______
15
16
×〔1÷(
2
3
+
1
2
)〕=______
21
26
×
13
7
+
1
2
)÷
5
9
=______
17
24
÷5+
1
5
÷
24
7
+0.2=______
4
7
÷〔(
5
6
-
4
5
)÷
7
16
〕=______
〔4-(
3
4
-
3
8
)〕÷
1
8
=______
8
15
÷〔
5
32
×(
9
10
+
1
6
)〕=______
3-
5
18
×
27
40
-
13
16
=______
2
21
÷〔(
3
4
-
2
3
)×
6
7
〕=______.
答案

7
8
-
15
32
÷
5
8
+
3
16

=

7
8
-
15
32
×
8
5
+
3
16

=

7
8
-
3
4
+
3
16

=

14
16
-
12
16
+
3
16

=

5
16

4
3
-
1
5
×
1
4
)÷
4
15

=(

4
3
-
1
20
)×
15
4

=

4
3
×
15
4
-
1
20
×
15
4

=5-

3
16

=4

13
16

4
5
×
5
18
+
3
7
+
7
9

=

2
9
+
3
7
+
7
9

=

2
9
+
7
9
+
3
7

=1+

3
7

=1

3
7

7
8
÷[(
7
8
-
3
4
)×
4
5
]

=

7
8
÷[(
7
8
-
6
8
)×
4
5
]

=

7
8
÷[
1
8
×
4
5
]

=

7
8
÷
1
10

=

7
8
×10

=

35
4

=8

3
4

6×(

2
15
+
1
12
)-
1
8

=

2
15
+
1
12
-
1
8

=

4
5
+
1
2
-
1
8

=

32
40
+
20
40
-
5
40

=

47
40

=1

7
40

2-

5
9
÷
2
3
-
1
6

=2-

5
9
×
3
2
-
1
6

=2-

5
6
-
1
6

=2-(

5
6
+
1
6

=2-1

=1;

7
3
-(
3
5
÷
9
20
+
8
23

=

7
3
-(
3
5
×
20
9
+
8
23

=

7
3
-(
4
3
+
8
23

=

7
3
-
4
3
-
8
23

=1-

8
23

=

15
23

[2-(

8
5
+
1
3
)]÷
4
15

=[2-(

24
15
+
5
15
)]÷
4
15

=[

30
15
-
29
15
4
15

=

1
15
÷
4
15

=

1
15
×
15
4

=

1
4

1-(

5
8
÷
3
2
+
1
4

=1-(

5
8
×
2
3
+
1
4

=1-(

5
12
+
3
12

=1-

8
12

=1-

2
3

=

1
3

5
7
÷
8
9
+
7
8
÷
7
5
-
5
7

=

5
7
×
9
8
+
7
8
×
5
7
-
5
7

=

5
7
×(
9
8
+
7
8
-1)

=

5
7
×1

=

5
7

(1-

1
3
÷
4
7
)×
3
10

=(1-

1
3
×
7
4
)×
3
10

=(1-

7
12
)×
3
10

=

5
12
×
3
10

=

1
8

3
5
-
3
5
×
5
9
)÷
4
9

=

3
5
×(1-
5
9
)×
9
4

=

3
5
×
4
9
×
9
4

=

3
5

[

5
6
-(
3
4
-
1
2
)]÷
7
15

=[

10
12
-(
9
12
-
6
12
)]÷
7
15

=[

10
12
-
9
12
+
6
12
7
15

=

7
12
×
15
7

=

5
4

=1

1
4

15
16
×[1÷(
2
3
+
1
2
)]

=

15
16
×[1÷(
4
6
+
3
6
)]

=

15
16
×[1÷
7
6
]

=

15
16
×1×
6
7

=

45
56

21
26
×
13
7
+
1
2
)÷
5
9

=(

21
26
×
13
7
+
1
2
)÷
5
9

=(

3
2
+
1
2
)×
9
5

=2×

9
5

=

18
5

=3

3
5

17
24
÷5+
1
5
÷
24
7
+0.2

=

17
24
×
1
5
+
1
5
×
7
24
+
1
5

=

1
5
×(
17
24
+
7
24
+1

=

1
5
×2

=

2
5

4
7
÷[(
5
6
-
4
5
)÷
7
16
]

=

4
7
÷[(
25
30
-
24
30
)×
16
7
]

=

4
7
÷
8
105

=

4
7
×
105
8

=

15
2

=7

1
2

[4-(

3
4
-
3
8
)]÷
1
8

=[4-(

6
8
-
3
8
)]÷
1
8

=[4-

3
8
1
8

=[4-

3
8
]×8

=4×8-

3
8
×8

=32-3

=29;

8
15
÷[
5
32
×(
9
10
+
1
6
)]

=

8
15
÷[
5
32
×(
27
30
+
5
30
)]

=

8
15
÷[
5
32
×
32
30
]

=

8
15
÷
1
6

=

8
15
×6

=

16
5

=3

1
5

3-

5
18
×
27
40
-
13
16

=3-

3
16
-
13
16

=3-(

3
16
+
13
16

=3-1

=2;

2
21
÷[(
3
4
-
2
3
)×
6
7
]

=

2
21
÷[(
9
12
-
8
12
)×
6
7
]

=

2
21
÷[
1
12
×
6
7
]

=

2
21
÷
1
14

=

2
21
×14

=1

1
3

选择题
填空题